Pengaruh Penggunaan Media E-learning Berbantuan Quizizz terhadap Hasil Belajar Siswa SMA Negeri 16 Semarang - Wibawanti, Diah; Benardi, Andi Irwan (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2021)
This study aims to analyze the use of e-learning media assisted by quizizz class XI IPS SMA Negeri 16 Semarang City and determine whether there is an effect of the use of media quizizz on the learning outcomes of class XI IPS SMA Negeri 16 Semarang City. Researchers collected data using questionnaires and test instruments. The data analysis technique used percentage descriptive analysis and the analysis used the t test. The results showed that the variable use of media was 84.68% which indicated that the use of e-learning media assisted by quizizz was classified (81% -100%) which showed a very high category. The variable learning outcomes t count on the test using the paired sample t-test sig (2 tailed) <0.05 indicates that if there is an influence on the post-test results of the experimental class using quizizz, the result is 81.72 while in the control class post-test the mean value - The average is 68 so that there is a significant effect. The conclusion of this study is